Ternary precursor and preparation method thereof
Patent Information
- Application Number
- CN202411817467.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The lithium ion conduction rate and electron conduction of existing high-nickel ternary precursor materials have low lithium ion conduction rate and poor cycling performance, and the problems of conventional large particle size and lack of microcrystal structure regulation.
A new synthesis method is adopted to control the temperature of the reactor and add hydrogen peroxide solution to form ternary precursor particles with loose cores and stacked shells of flat sheet structures to ensure that their XRD diffraction peak intensity I(101)/I(001)>1.3 and FWHM(101)<0.5.
It improves the transmission characteristics and storage capabilities of lithium ions, improves the rate performance and discharge capacity, and obtains ternary positive electrode materials with better performance.
Smart Images

Figure CN119637963A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery material preparation, and in particular to a ternary precursor and a preparation method thereof. Background Art
[0002] As the application of lithium-ion batteries in the field of new energy vehicles gradually expands, cruising range has become a key factor restricting the development of new energy vehicles. Improving the energy density of lithium-ion batteries is an effective way to solve the range anxiety. High-nickel ternary layered materials have the advantages of high specific capacity, low cost and relatively good safety. They are considered to be one of the most promising high-energy-density lithium-ion battery positive electrode materials.
[0003] The precursor is the pre-production process of the positive electrode processing, and the quality of the precursor directly determines the physical and chemical indicators of the final sintered product. The production of ternary precursors is different from that of lithium cobalt oxide and lithium iron phosphate. The hydroxide co-precipitation method is used to synthesize cobalt salt, nickel salt and manganese salt in a reactor in a certain proportion, which can easily control the particle size, specific surface area, morphology and tap density of the precursor.
[0004] For high-nickel ternary precursors, nickel can increase capacity, but due to the influence of crystal structure and internal Li / Ni mixing, it is difficult for lithium ions to escape, resulting in a low initial discharge capacity and low first-cycle coulomb efficiency. In addition, the low lithium ion conduction rate and electronic conductivity make the rate performance poor. At the same time, the long lithium ion migration path makes it difficult for lithium ions to be deintercalated, affecting its cycle performance.
[0005] Ordered crystal structure and particle morphology that is conducive to lithium ion transmission channels can improve the discharge capacity and cycle performance of high-nickel materials. At present, precursors with various morphologies have been reported, such as radial, core-shell structure, hollow structure, coating, etc., which can improve the performance of the precursor to a certain extent. For example, CN113299904B synthesizes high-nickel precursors with different radial morphologies to improve their thermal stability; Patent CN115557541A uses core-shell structure to solve the ball cracking phenomenon caused by the inability of water to effectively overflow during the drying process of high-nickel ternary precursors, as well as the technical problems of lithium ion migration and mixing during subsequent calcination; Patent CN114560512B uses coating to effectively prevent the electrolyte from corroding the active positive electrode by side reactions. However, the high-nickel ternary precursors reported so far are conventional large particle sizes (9~15 microns), while the preparation process of small particle products (3~6 microns) for single crystal materials is relatively small, and is mainly regulated by macroscopic morphology, lacking research on crystal structure. Therefore, it is necessary to further improve the existing technology and a new synthesis method is needed to obtain a precursor with better macroscopic morphology and microscopic crystal structure.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The object of the present invention is to provide a ternary precursor and a preparation method thereof, aiming to improve at least one problem mentioned in the background technology.
[0008] The present invention is achieved in that: In a first aspect, the present invention provides a ternary precursor, wherein the particles of the precursor include a core and an outer shell, wherein the core is loose relative to the outer shell, and the outer shell is formed by inserting and stacking flat sheet structures along the radial direction of the particles of the precursor, wherein each plurality of sheet structures in the outer shell are stacked in parallel (the so-called "parallel" here and hereinafter means that the edges of the sheet structures located on the surface are parallel to each other as seen from the outer surface of the precursor); The XRD diffraction peak intensity of the ternary precursor is I(101) / I(001)>1.3, FWHM(101)<0.5; The general chemical formula of the ternary precursor is Ni x Co y Mn z (OH) 2 , where x+y+z=1, 0.8≤x<1, 0 <y<0.2,0<z<0.2。
[0009] In an optional embodiment, to ensure that the precursor has better electrochemical performance after being made into a positive electrode material, the particle size of the core is 1-2 μm, and the diameter of the precursor particles is 3-6 μm; In a second aspect, the present invention provides a method for preparing a ternary precursor according to the aforementioned embodiment, comprising: The temperature of the reactor with the bottom liquid is controlled to be 50-65°C, and the metal salt solution, the precipitant solution and the complexing agent solution are continuously added into the reactor in parallel; After the core is generated, add hydrogen peroxide solution into the reactor, and at the same time, increase the temperature of the reactor by 5-10°C; The reaction is stopped after the particles in the reactor grow to the target particle size; The metal salt solution is a salt solution containing nickel ions, cobalt ions and manganese ions; Hydrogen peroxide is dissolved in the base solution.
[0010] In an optional embodiment, to ensure that a precursor with better performance can be obtained, the pH of the base liquid is 11~12; the base liquid contains a chelating agent, and the chelating agent is selected from at least one of ammonia water and ammonium salt, and the ammonia value in the base liquid is 2~8g / L; the concentration of hydrogen peroxide in the base liquid is 1~3 mol / L.
[0011] In an optional embodiment, the invention further comprises at least one of the following features (1) or 2: (1) The solute in the metal salt solution is selected from at least one of sulfate, nitrate and halogen salt; The precipitant is selected from at least one of a sodium hydroxide solution and a potassium hydroxide solution; (2) The total concentration of metal ions in the metal salt solution is 1~3 mol / L, the concentration of the complexing agent solution is 4~12 mol / L, the concentration of the precipitant solution is 4~12 mol / L, and the concentration of the hydrogen peroxide solution is 4~12 mol / L.
[0012] In an optional embodiment, to ensure that a precursor with better performance can be obtained, the pH in the reactor is controlled to be 11-12 during the precipitation process, and the ammonia value in the reactor is controlled to be 2-8 g / L. During the reaction, the materials are added in a ratio of 1-5:1 according to the molar ratio of metal ions in the metal salt solution to hydrogen peroxide in the hydrogen peroxide solution.
[0013] In an alternative embodiment, a primary slurry is obtained after stopping the reaction; Aging the primary slurry for 2 to 8 hours to obtain the final slurry; The final slurry is subjected to solid-liquid separation, and the obtained solid material is washed and then dried.
[0014] The present invention has the following beneficial effects: The ternary precursor provided by the present invention is different from the conventional radial structure. Its core is loose, and its shell is formed by inserting and stacking flat sheet structures. Each plurality of sheet structures in the shell are stacked in parallel, so its particles have obvious pores from the outside to the inside. This structure is conducive to lithium ion transmission and improves crystallinity; and its XRD diffraction peak intensity I(101) / I(001)>1.3 indicates that the (101) crystal plane is the dominant crystal plane, which is conducive to improving the transmission characteristics of lithium ions and has better rate performance; FWHM (101) <0.5 indicates that it can have more sheet layers, which is conducive to the storage of lithium ions. The inventor speculates that the reason why the FWHM (101) value is small is related to the structural characteristics of each plurality of sheet structures stacked in parallel. The precursor provided by the present invention improves the problem of lithium ion transmission rate of high-nickel ternary positive electrode materials by regulating the microscopic crystal structure. This structure is conducive to lithium ion channel transmission and improves crystallinity, so that it has high rate performance and high capacity characteristics.
[0015] The preparation method provided by the present invention can make the inner core obtain a relatively loose structure by adding hydrogen peroxide to the base liquid to provide a micro-oxidation environment. If it is continuously added in the early stage of precipitation, it is not conducive to improving the tap density. After the inner core is formed, hydrogen peroxide is added to the reaction system again to refine the primary particles, and at the same time, the reaction temperature is increased while the original pH value is maintained unchanged. In theory, the pH decreases with the increase of temperature. Maintaining the original pH value unchanged means that more precipitants will be introduced, so high temperature and more hydroxides will make the particles have stronger surface activity. Under such synergistic effect, it is beneficial to improve the macroscopic and microscopic structures of the particles, and obtain a precursor with a loose inner core at the macroscopic level, a flat sheet structure inserted radially, an outer shell with multiple sheet structures stacked in parallel, and a crystal structure with characteristic diffraction peaks at the microscopic level.
[0016] Therefore, the positive electrode material prepared from the ternary precursor provided by the embodiment of the present invention has higher rate performance and higher capacity after being assembled into a battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 is a SEM image of the precursor particles prepared in Example 1; Figure 2 is a SEM image of a cross section of the precursor particles prepared in Example 1; Figure 3 is a SEM image of the precursor particles prepared in Comparative Example 1; Figure 4 is a SEM image of a cross section of the precursor particles prepared in Comparative Example 1; Figure 5 This is the XRD pattern of the precursor prepared in Example 1; Figure 6 This is the XRD pattern of the precursor prepared in Comparative Example 1. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0020] Example 1 (1) Preparation of materials: nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 80:15:5, and pure water is added to stir and dissolve to prepare a mixed solution of nickel, cobalt and manganese salts with a concentration of 2 mol / L. At the same time, 10 mol / L sodium hydroxide solution is prepared as a precipitant, 8 mol / L ammonia water is prepared as a complexing agent, and 6 mol / L hydrogen peroxide solution is prepared as an additive; (2) Prepare the bottom liquid of the reactor: add pure water to 1 / 2 of the liquid level in the reactor, heat the system to 60°C and maintain, then add the precipitant solution to adjust the pH value to 11.6-11.7, add the complexing agent solution to control the ammonia value in the reactor to 5g / L, and add the additive to control the concentration in the reactor to 2mol / L; (3) The mixed salt solution is added to the reactor at a flow rate of 70 ml / min, and a precipitant and a complexing agent are added at the same time, maintaining the concentration of the complexing agent at 5 g / L. The coprecipitation reaction is carried out at a stirring speed of 600 rpm and under the protection of inert gas, and the pH of the reactor is maintained at 11.6-11.7 until the D50 of the particles in the reactor is detected to grow to 1.5 microns to obtain an inner core; after the inner core is formed, the additive is added at a molar ratio of 2:1 between the metal salt solution and the additive solution, and the temperature of the reactor is raised by 10°C, while the pH and other parameters are kept unchanged, and the reaction is continued until the D50 of the particles grows to 3 microns; (4) The obtained material is aged for 2 hours. After the aging is completed, the material is pumped into a centrifuge for washing. After the sodium sulfur content is qualified, the filter cake is sent to an oven to be dried at 120°C. After the moisture content is qualified, it is sieved using a vibrating screen to obtain a ternary precursor with a special structure. The particle size D50 of the precursor is 3 μm.
[0021] The SEM image of the prepared precursor and its cross section is as follows: Figure 1 and Figure 2 As shown in the figure, it can be seen that the core of the precursor particle is loose relative to the shell, and the shell is composed of a flat sheet structure inserted along the radial direction of the precursor particle, and each plurality of sheet structures are stacked in parallel; its diffraction peak is as follows Figure 5 As shown, the (101) crystal plane is the dominant plane.
[0022] Example 2 (1) Preparation: nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 85:10:5, and pure water is added to stir and dissolve to prepare a mixed solution of nickel, cobalt and manganese salts with a concentration of 2 mol / L. At the same time, 10 mol / L sodium hydroxide solution is prepared as a precipitant, 8 mol / L ammonia water is prepared as a complexing agent, and 6 mol / L hydrogen peroxide solution is prepared as an additive; (2) Preparation of reactor bottom liquid: Add pure water to the reactor to 1 / 2 liquid level, heat the system to 60°C and maintain, then add precipitant solution to adjust the pH value to 11.4-11.5, add complexing agent solution to control the ammonia value in the reactor to 3g / L, and add additives to control the concentration in the reactor to 3mol / L; (3) The mixed salt solution is added to the reactor at a flow rate of 70 ml / min, and a precipitant and a complexing agent are added at the same time, maintaining the concentration of the complexing agent at 3 g / L. The coprecipitation reaction is carried out at a stirring speed of 600 rpm and under the protection of inert gas, and the pH of the reactor is maintained at 11.4-11.5 until the D50 of the particles in the reactor is detected to grow to 1.5 microns, thereby obtaining the inner core; after the inner core is formed, the additive is added at a molar ratio of 3:1 between the metal salt solution and the additive solution, and the temperature of the reactor is raised by 10°C and maintained, while the pH and other parameters remain unchanged, and the reaction is continued until the D50 of the particles grows to 3.5 microns.
[0023] (4) The obtained material is aged for 2 hours. After the aging is completed, the material is pumped into a centrifuge for washing. After the sodium sulfur content is qualified, the filter cake is sent to an oven to be dried at 120°C. After the moisture content is qualified, it is sieved using a vibrating screen to obtain a ternary precursor with a special structure. The particle size D50 of the precursor is 3.5 μm.
[0024] Example 3 (1) Preparation of materials: nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 90:5:5, and pure water is added to stir and dissolve to prepare a mixed solution of nickel, cobalt and manganese salts with a concentration of 2 mol / L. At the same time, 12 mol / L sodium hydroxide solution is prepared as a precipitant, 6 mol / L ammonia water is prepared as a complexing agent, and 8 mol / L hydrogen peroxide solution is prepared as an additive; (2) Prepare the bottom liquid of the reactor: add pure water to 1 / 2 of the liquid level in the reactor, heat the system to 55°C and maintain, then add the precipitant solution to adjust the pH value to 11.7-11.8, add the complexing agent solution to control the ammonia value in the reactor to 5g / L, and add the additive to control the concentration in the reactor to 3mol / L; (3) The mixed salt solution is added to the reactor at a flow rate of 70 ml / min, and a precipitant and a complexing agent are added at the same time, maintaining the concentration of the complexing agent at 3 g / L. The co-precipitation reaction is carried out at a stirring speed of 600 rpm and under the protection of inert gas, and the pH of the reactor is maintained at 11.7-11.8 until the D50 of the particles in the reactor is detected to grow to 2.0 μm, thereby obtaining an inner core. After the inner core is formed, an additive is added at a molar ratio of 5:1 between the metal salt solution and the additive solution, and the temperature of the reactor is raised by 5°C, while the pH and other parameters are maintained unchanged, and the reaction is continued until the D50 of the particles grows to 4.0 μm.
[0025] (4) The obtained material is aged for 2 hours. After the aging is completed, the material is pumped into a centrifuge for washing. After the sodium sulfur content is qualified, the filter cake is sent to an oven to be dried at 120°C. After the moisture content is qualified, it is sieved using a vibrating screen to obtain a ternary precursor with a special structure. The particle size D50 of the precursor is 4.0 μm.
[0026] Comparative Example 1 This comparative example does not add additives (hydrogen peroxide) and the precipitation process does not heat up. Specifically: (1) Preparation: nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 80:15:5, and pure water is added to stir and dissolve to prepare a mixed solution of nickel, cobalt and manganese salts with a concentration of 2 mol / L. At the same time, 10 mol / L sodium hydroxide solution is prepared as a precipitant and 8 mol / L ammonia water is prepared as a complexing agent; (2) Prepare the bottom liquid of the reactor: add pure water to 1 / 2 of the liquid level in the reactor, heat the system to 60°C and maintain, then add the precipitant solution to adjust the pH value to 11.6-11.7, and add the complexing agent solution to control the ammonia value in the reactor to 5g / L; (3) adding the mixed salt solution into the reactor at a flow rate of 70 ml / min, adding a precipitant and a complexing agent at the same time, maintaining the concentration of the complexing agent at 5 g / L, and carrying out a coprecipitation reaction at a stirring speed of 600 rpm under inert gas protection, maintaining the pH of the reactor at 11.6-11.7, until particles with a D50 of 3 μm are generated; (4) The obtained material is aged for 2 hours. After the aging is completed, the material is pumped into a centrifuge for washing. After the sodium sulfur is qualified, the filter cake is sent to an oven to be dried at 120°C. After the moisture content is qualified, it is sieved using a vibrating screen to obtain a precursor with a special structure. The particle size D50 of the precursor is 3 μm.
[0027] The SEM image of the prepared precursor and its cross section is as follows: Figure 3 and Figure 4 As shown in the figure, it can be seen that the core of the precursor particle is not looser than the shell, and the stacked structure of the shell is arranged in a disordered manner. Its diffraction peak is as follows Figure 6 As shown, the (100) crystal plane is the dominant plane.
[0028] Comparative Example 2 In this comparative example, an additive (hydrogen peroxide) is added, but the temperature is not increased during the precipitation process, specifically: (1) Preparation of materials: nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 80:15:5, and pure water is added to stir and dissolve to prepare a mixed solution of nickel, cobalt and manganese salts with a concentration of 2 mol / L. At the same time, 10 mol / L sodium hydroxide solution is prepared as a precipitant, 8 mol / L ammonia water is prepared as a complexing agent, and 6 mol / L hydrogen peroxide solution is prepared as an additive; (2) Prepare the bottom liquid of the reactor: add pure water to 1 / 2 of the liquid level in the reactor, heat the system to 60°C and maintain, then add the precipitant solution to adjust the pH value to 11.6-11.7, add the complexing agent solution to control the ammonia value in the reactor to 5g / L, and add the additive to control the concentration in the reactor to 2mol / L; (3) The mixed salt solution is added to the reactor at a flow rate of 70 ml / min, and a precipitant and a complexing agent are added at the same time, and the concentration of the complexing agent is maintained at 5 g / L. The coprecipitation reaction is carried out at a stirring speed of 600 rpm and under the protection of inert gas, and the pH of the reactor is maintained at 11.6-11.7 until the D50 of the particles in the reactor is detected to grow to 1.5 microns, and the inner core is obtained; after the inner core is formed, the additive is added at a molar ratio of 2:1 between the metal salt solution and the additive solution, and the temperature, pH and other parameters are maintained unchanged, and the reaction is continued until the D50 of the particles grows to 3 microns; (4) The obtained material is aged for 2 hours. After the aging is completed, the material is pumped into a centrifuge for washing. After the sodium sulfur content is qualified, the filter cake is sent to an oven to be dried at 120°C. After the moisture content is qualified, it is sieved using a vibrating screen to obtain a ternary precursor with a special structure. The particle size D50 of the precursor is 3 μm.
[0029] Comparative Example 3 This comparative example does not add additives (hydrogen peroxide), but the precipitation process is heated up, specifically: (1) Preparation: nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 80:15:5, and pure water is added to stir and dissolve to prepare a mixed solution of nickel, cobalt and manganese salts with a concentration of 2 mol / L. At the same time, 10 mol / L sodium hydroxide solution is prepared as a precipitant and 8 mol / L ammonia water is prepared as a complexing agent; (2) Prepare the bottom liquid of the reactor: add pure water to 1 / 2 of the liquid level in the reactor, heat the system to 60°C and maintain, then add the precipitant solution to adjust the pH value to 11.6-11.7, add the complexing agent solution to control the ammonia value in the reactor to 5g / L, and add the additive to control the concentration in the reactor to 2mol / L; (3) The mixed salt solution was added to the reactor at a flow rate of 70 ml / min, and a precipitant and a complexing agent were added at the same time. The concentration of the complexing agent was maintained at 5 g / L. The coprecipitation reaction was carried out at a stirring speed of 600 rpm and under the protection of an inert gas. The pH of the reactor was maintained at 11.6-11.7 until the D50 of the particles in the reactor was detected to grow to 1.5 μm, and the inner core was obtained. After the inner core was formed, the temperature of the reactor was raised by 10°C and maintained, and the pH and other parameters were kept unchanged. The reaction was continued until the D50 of the particles grew to 3 μm. (4) The obtained material is aged for 2 hours. After the aging is completed, the material is pumped into a centrifuge for washing. After the sodium sulfur content is qualified, the filter cake is sent to an oven to be dried at 120°C. After the moisture content is qualified, it is sieved using a vibrating screen to obtain a ternary precursor with a special structure. The particle size D50 of the precursor is 3 μm.
[0030] Experimental example The precursors prepared in each embodiment and comparative example were prepared with an XRD diffractometer to obtain XRD patterns, such as Figure 5 and Figure 6 As shown. And according to Figure 5-Figure 6 I101 / I001 and FWHM(101) were calculated and the results are recorded in Table 1.
[0031] Table 1 Physical and chemical indicators of the precursors prepared in various embodiments and comparative examples
[0032] from Figure 5 , Figure 6 As can be seen from Table 1, the XRD diffraction peak intensity ratio of the precursors prepared in various embodiments of the present invention is I(101) / I(001)>1.3, indicating that the (101) crystal plane is the dominant crystal plane, which is beneficial to improving the transmission characteristics of lithium ions and has better rate performance; the FWHM (101) is lower, indicating that it can have more flakes, which is beneficial to the storage of lithium ions and has a higher discharge capacity.
[0033] As can be seen from Table 1, the XRD diffraction peak intensity ratio I(101) / I(001) of the precursors prepared in the comparative examples of the present invention is significantly smaller than that of the embodiments, and the FWHM(101) is higher. This shows that in the precursor preparation process, adding hydrogen peroxide after nucleation and increasing the temperature are indispensable, and adding hydrogen peroxide to the base liquid is indispensable. If hydrogen peroxide is not added after nucleation or the temperature is not increased, this synergistic effect cannot be obtained.
[0034] In summary, the ternary precursor provided by the present invention is different from the conventional radial structure. Its core is loose, and its shell is formed by parallel insertion and stacking of flat sheet structures. Therefore, its particles have obvious pores from the outside to the inside. This structure is conducive to lithium ion transmission and improved crystallinity; and its XRD diffraction peak intensity I(101) / I(001)>1.3 indicates that the (101) crystal plane is the dominant crystal plane, which is conducive to improving the transmission characteristics of lithium ions and has better rate performance; FWHM (101) <0.5, indicating that it can have more sheet layers, which is conducive to the storage of lithium ions. Therefore, the positive electrode material prepared by the ternary precursor provided by the embodiment of the present invention has a higher rate performance and higher capacity after being assembled into a battery.
[0035] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A ternary precursor, characterized in that: The precursor particles include a core and an outer shell, wherein the core is loose relative to the outer shell, and the outer shell is formed by inserting and stacking flat sheet structures along the radial direction of the precursor particles, and each plurality of sheet structures in the outer shell are stacked in parallel; The XRD diffraction peak intensity of the ternary precursor is I(101) / I(001)>1.3, FWHM(101)<0.5; The chemical formula of the ternary precursor is Ni x Co y Mn z (OH)2, where x+y+z=1, 0.8≤x<1, 0 <y<0.2,0<z<0.2。 2. The ternary precursor according to claim 1, characterized in that: The particle size of the core is 1-2 μm, and the diameter of the precursor particles is 3-6 μm.
3. A method for preparing the ternary precursor as claimed in claim 1 or 2, characterized in that: include: The temperature of the reaction kettle with the bottom liquid is controlled to be 50-65° C., and a metal salt solution, a precipitant solution and a complexing agent solution are continuously added into the reaction kettle in parallel; After the inner core is generated, a hydrogen peroxide solution is added into the reactor, and while adding the hydrogen peroxide solution, the temperature of the reactor is raised by 5-10° C.; After the particles in the reactor grow to a target particle size, the reaction is stopped; The metal salt solution is a salt solution containing nickel ions, cobalt ions and manganese ions; Hydrogen peroxide is dissolved in the base liquid.
4. The preparation method according to claim 3, characterized in that: The pH of the base solution is 11-12; The base liquid contains a complexing agent, the complexing agent is selected from at least one of ammonia water and ammonium salt, and the ammonia value in the base liquid is 2-8 g / L; The concentration of hydrogen peroxide in the base solution is 1-3 mol / L.
5. The preparation method according to claim 3, characterized in that: Also includes at least one of the following features (1) or 2: (1) The solute in the metal salt solution is selected from at least one of sulfate, nitrate and halogen salt; The precipitant is selected from at least one of a sodium hydroxide solution and a potassium hydroxide solution; (2) The total concentration of metal ions in the metal salt solution is 1-3 mol / L, the concentration of the complexing agent solution is 4-12 mol / L, the concentration of the precipitant solution is 4-12 mol / L, and the concentration of the hydrogen peroxide solution is 4-12 mol / L.
6. The preparation method according to claim 5, characterized in that: During the precipitation process, the pH in the reactor is controlled to be 11-12, and the ammonia value in the reactor is controlled to be 2-8 g / L. During the reaction process, materials are added in a ratio of 1-5:1 to the molar ratio of metal ions in the metal salt solution to hydrogen peroxide in the hydrogen peroxide solution.
7. The preparation method according to claim 3, characterized in that: After stopping the reaction, a primary slurry is obtained; Aging the primary slurry for 2 to 8 hours to obtain a final slurry; The final slurry is subjected to solid-liquid separation, and the obtained solid material is washed and then dried.
Citation Information
Patent Citations
A high-nickel precursor material, its preparation method and application
CN113299904B